Therapeutic Effects of Milk Thistle (Silybum marianum L.) and Artichoke (Cynara scolymus L.) on Nonalcoholic Fatty Liver Disease in Type 2 Diabetic Rats. (11th February 2022) - Doostkam, Aida; Fathalipour, Mohammad; Anbardar, Mohammad Hossein; Purkhosrow, Azar; Mirkhani, Hossein
Abstract : Background . At present, nonalcoholic fatty liver disease (NAFLD) does not have an approved pharmacologic therapy. The present study investigated the protective effects and possible mechanisms of milk thistle ( Silybum marianum L.) and artichoke ( Cynara scolymus L.) in treating NAFLD in type 2 diabetic rats. Methods . The NAFLD was established in rats after four weeks of type 2 diabetes induction. The animals were treated with pharmaceutical preparations of milk thistle (Livergol®) and artichoke (Atheromod-B®) extracts for eight weeks. After the end of the intervention, oral glucose tolerance, the serum parameters of oxidative stress, liver functional tests, and lipid profiles were evaluated. Histopathological changes were assessed by hematoxylin and eosin staining. Results . Treatment with preparations of milk thistle and artichoke nonsignificantly improved glucose tolerance in diabetic rats. Both preparations significantly improved serum superoxide dismutase activity and the level of malondialdehyde. Although treatment with milk thistle reduced serum activity of aspartate aminotransferase and serum levels of triglyceride (TG), total cholesterol, and low-density lipoprotein-cholesterol, artichoke extracts only attenuated the serum level of TG. Milk thistle also effectively protected the liver from histological changes. Conclusions . Milk thistle could be a promising pharmacological option for the treatment of NAFLD. Nonetheless, long-term randomized clinical trials are necessary to confirm the observed results.